Investigating Individual Pathways to Recovery - McBride, Mackenzie R (2017)
Drug use is most prevalent among young adults between ages 18 and 24; this is just one factor that contributes to the high rates of substance use on college campuses. Collegiate recovery programs (CRPs) have been growing in number, awakening the “youth in recovery” movement. This paper presents literature on various tools and elements of recovery, with a focus on CRPs and their significance. This study aims to fill the knowledge gap by examining individual pathways to recovery and learning about the characteristics of students participating in CRPs, including their life events and decisions to seek treatment. Semi-structured interviews were conducted with 15 students in a CRP at a large university located in the southeastern region of the United States. The results describe the participants’ personal experiences and reasons for using alcohol and other drugs such as peer pressure and family adversity, in addition to reasons for seeking treatment. Many participants reported spirituality/religion, hobbies, and involvement in the recovery community as important tools for sustaining recovery. Participants also discussed the challenges of living in recovery including fear of stigma and time management. Overall, college students in recovery describe CRPs are beneficial as they offer a sense of community, support, and motivation. Implications are discussed with hopes to help guide decisions about whether these programs should be expanded to other institutions